LARVAL PHASE OF Spermologus rufus BOHEMAN (COLEOPTERA: CURCULIONIDAE) - BARRETO, Marliton Rocha; dos ANJOS, Norivaldo (Scientia Agraria, 2000)
Works were realized in Forest Entomology laboratory of Viçosa Federal University, in Viçosa, MG, under controlled condictions. In this survey, larval phase of Spermologus rufus was characterized, with the purpose of obtain useful knowledge to control of this insect. Quantity of larval instars, morphology description, duration and viability of ínstars larval, and behvior of feeding and defense were determined. It was verified in the morphology study that after their eclosion, larvae were subculindrical, little incurvated and with light bege colour. According to the values found, S. rufus larvae present three larval instars. Larval period varied from three to 24 days. The larvae were found in the internal seed portion. After eclosion, the remained in this same place, where feeding the endosperm until changed in adults. The larvae showed negative phototaxis.